Frequency-selective excitation of guided acoustic modes in a photonic crystal fiber - Stiller, Birgit; Delque, M.; Beugnot, J. -C.; Lee, M. W.; Melin, G.; Maillotte, H.; Laude, Vincent; Sylvestre, Thibaut (Optics Express, 2011)
We present experimental and numerical results demonstrating the simultaneous frequency-selective excitation of several guided acoustic Brillouin modes in a photonic crystal fiber with a multi-scale structure design. These guided acoustic modes are identified by using a full vector finite-element model to result from elastic radial vibrations confined by the wavelength-scale air-silica microstructure. We further show the strong impact of structural irregularities of the fiber on the frequency and modal shape of these acoustic resonances. © 2011 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-29